2016
DOI: 10.2323/jgam.62.14
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of dark culture condition for enlargement of spheroplasts of the aerobic anoxygenic photosynthetic marine bacterium <i>Erythrobacter litoralis</i>

Abstract: None of the authors of this manuscript has any financial or personal relationship with other people or organizations that could inappropriately influence their work.Erythrobacter are rod shaped and approximately 0.4-0.5 × 1.0-5.0 µm in size (Yurkov and Beatty, 1998).Incubation of spheroplasts formed by lysozymes with penicillin, an inhibitor of peptidoglycan synthesis, was shown to generate giant protoplasts (Kuroda et al., 1998;Kusaka, 1967;Nakamura et al., 2011). Although DNA replication is generally related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The dark condition promoted the accumulation of BChl [29]. Results indicated that dark culture condition was required for the enlargement of spheroplasts of Erythrobacter litoralis and known marine AAP bacterium, and the enlargement was inhibited under continuous light [30].…”
Section: Diversity Of Pufm Gene Populationsmentioning
confidence: 96%
“…The dark condition promoted the accumulation of BChl [29]. Results indicated that dark culture condition was required for the enlargement of spheroplasts of Erythrobacter litoralis and known marine AAP bacterium, and the enlargement was inhibited under continuous light [30].…”
Section: Diversity Of Pufm Gene Populationsmentioning
confidence: 96%
“…Although continuous light inhibited the enlargement of E. litoralis spheroplasts (Takayanagi et al, 2016), these cells are enlarged under both anaerobic and aerobic lightdark (12 h each) conditions (Nakazawa and Nishida, 2017). In addition, E. litoralis spheroplasts did not enlarge under blue light but were enlarged under green and red lights at 144 h of growth (under light-dark conditions, each 12 h) (Nishino and Nishida, 2017).…”
mentioning
confidence: 98%
“…litoralis spheroplasts were prepared using a method described by Takayanagi et al (2016). Briefly, E. litoralis spheroplasts were incubated at 25∞C in dark, light-dark (12 h each), and light conditions.…”
mentioning
confidence: 99%